Effect of Atlantis Herbicide on Milk Thistle Weed (Syllibium Marianum) Under Spraying Growth Stages Differ - Hamad, Abdulmueen Shabeeb; Mawlood, Ghadeer Mukhles; Hayawi, Jasim Abdullah (American Journal of Botany and Bioengineering, 2025)
The research was conducted in the College of Agricultural Technology during 2022 / 2023 to study effect of Atlantis herbicide on the Milk thistle weed (Syllibium marianum) when spraying stages differed. The research incorporated several factors, with the first being the concept of Atlantis herbicide concentrations (recommended concentration, higher than the recommended concentration, less than the recommended concentration, as well as the comparison treatment). The second factor: timing of spraying the herbicide (cotyledonous leaf stage, four-leaf stage, pre-flowering stage), The Milk thistle weed seeds collected from the previous season 2021/2022 were planted in the pots have a diameter of 30 cm and a height of (30) cm, after filling them soil with ten seeds per pots, which were thinned to five plants, leaving (5) cm at the top. For the purpose of irrigation. A completely randomized design (CRD) was used in planning and implementing the research, with three replications (Al-Rawi and Khalafallah, 1980). The data were analyzed statistically by computer and using the SAS system, the multiple-range test (Duncan, 1955) was utilized to compare significantly different means. were distinguished. At a probability level of 0.05 with various letters of the alphabet. The results showed: Increasing the concentration of Atlantis herbicide from (0 to 400) gm.ha-1 was accompanied by a clear and significant effect on Syllibium marianum plants, as the degree of impact reached (8) degrees at the concentration is high at 400. g.ha-1, and there was also the Syllibium marianum species has experienced a gradual and substantial decrease in height plant and the number of its roots increased with increasing concentration of the herbicide, as the number of germs reached zero at the high concentration, and the wet and dry weight of the Syllibium marianum L. plant decreased at the same concentration, reaching (3.88 and 0.94) grams for the two plants, respectively. Early herbicide spray significantly affected plant shoots, while late spray increased plant height, number of shoots, and weight, reaching 38.50 cm, 3.16 g., 16.66 g., and 6.25 g. respectively. The interaction between the concentrations of (300) g.ha-1 and (400) g.ha-1 are being studied and spraying at cotyledon stage caused killing of the cotyledon plants. The interaction between the concentration (400) g.ha-1 and spraying in four-leaf stage achieved the lowest plant height, as it reached (4 cm), and the interaction between the concentration (300) g.ha-1 and spraying in the four-leaf stage recorded the lowest number of cuts, as it reached (1.33) tillers. The interaction between the concentration (400) g.ha-1 and spraying at the four-leaf stage achieved the lowest wet weight and the lowest dry weight of the Syllibium marianum plants, reaching (2.33 g and 0.53 g), respectively.